2020
DOI: 10.3390/app10217692
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Use of Geomorphic Elements Mapping to Characterize Subaqueous Bedforms Using Multibeam Bathymetric Data in River System

Abstract: Riverbed micro-topographical features, such as crest and trough, flat bed, and scour pit, indicate the evolution of fluvial geomorphology, and have an influence on the stability of underwater structures and overall scour pits. Previous studies on bedform feature extraction have focused mainly on the rhythmic bed surface morphology and have extracted crest and trough, while flat bed and scour pit have been ignored. In this study, to extend the feature description of riverbeds, geomorphic elements mapping was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Geomorphon analysis [32], a technique that we employ in this research, is a machine vision terrain classifier of rasterized terrain models. Geomorphons have been often used to represent and even predict geomorphological and hydrological changes in river valleys [33][34][35][36]. In the form of input to a physically based hydrological model, geomorphons were successfully represented in the spatially distributed hydrological parameters of the upper reaches of a montane watershed in Brazil [33].…”
Section: Core Of Cranberry Gladesmentioning
confidence: 99%
See 1 more Smart Citation
“…Geomorphon analysis [32], a technique that we employ in this research, is a machine vision terrain classifier of rasterized terrain models. Geomorphons have been often used to represent and even predict geomorphological and hydrological changes in river valleys [33][34][35][36]. In the form of input to a physically based hydrological model, geomorphons were successfully represented in the spatially distributed hydrological parameters of the upper reaches of a montane watershed in Brazil [33].…”
Section: Core Of Cranberry Gladesmentioning
confidence: 99%
“…In the form of input to a physically based hydrological model, geomorphons were successfully represented in the spatially distributed hydrological parameters of the upper reaches of a montane watershed in Brazil [33]. Yan et al (2020) found geomorphons to be optimal in the characterization of subaqueous riverbed features on the Yangtze River, China [35]; while the work of Gioia et al (2021) showed geomorphon-based classification to be a robust tool for the identification of geomorphological landscape elements at a large scale in southern Italy [37].…”
Section: Core Of Cranberry Gladesmentioning
confidence: 99%
“…[23] analysed longitudinal profiles to identify a change in derivatives signs while [24], also using longitudinal profiles, used the position of local minima and maxima. Other authors have attempted to use spatial classes (e.g., [25][26][27][28][29]), building on concepts such as geomorphons [30], topographic signatures [31] or index [32], that are then converted into individual features. Finally, other authors explored the delineation of crestline areas by skeletonization using triangular irregular network [33] and polygon breaking algorithms [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al (2020) [2] describe an interesting approach of the semi-automatic extraction of subaqueous landforms using multibeam bathymetric data. The comparison of three different methods of landform classification (i.e., Wood's criteria, SOM, and geomorphons) highlights that the geomorphon method has the highest degree of accuracy for the automatic extraction of the bedforms of a delta system in China.…”
mentioning
confidence: 99%